KKN TEMATIK NEW NORMAL COVID-19 - Rinaldi, Rinaldi; Prasetyo Rakhmadi, Herlambang Dwi (Gemi: Jurnal Penelitian dan Pengabdian, 2021)
The Real Work Lecture (KKN) of Cokroaminoto University Yogyakarta in 2021 is a thematic KKN, due to the Covid-19 pandemic, there are still some restrictions on community activities. The 2019 Corona Virus Pandemic or known as COVID-19 has greatly impacted people's lives, both economically and in the behavior of people's lives. This activity is aimed at preventing Covid-19 activities and not causing crowds. The contents of this activity are mostly aimed at building better health and distributing basic necessities to the community in the Umbulharjo District.